Assessment of Factors Affecting the Acceptance of Agricultural Innovations in Zurmi Local Government Area Zamfara State Nigeria (Global Journal of Science Frontier Research, 2014)
The aim of this paper is to assess the factors affecting acceptance of agricultural innovations in Zurmi Local Government Area of Zamfara State of Nigeria. The researcher investigated why new innovations were rejected and the role of government in motivating farmers to accept new innovations. A total sample of 80 respondents was selected out of the selected six wards, to represent the entire local government. Data was analysed using various statistical tools like frequencies, percentages and direct response. The major conclusions drawn from this paper were data regarding responses to new innovations have shown that 28 (35%) of the respondents accepted new innovations while 52 (65%) rejected the idea. Survey results regarding why new innovations were rejected revealed that 27 (33.7%) of the respondents reported poor roads is responsible, while 13 (16.2%) were not interested in accepting new innovations at all. Similarly, 40 (50%) reported financial constraints is responsible for not accepting new innovations. Perception of respondents regarding what should government do to encourage farmers to accept new innovations revealed that majority of the farmers 48 (60%) agreed that government should give loans to them. Similarly, 22 (27.5%) agreed that more extension advice should be delivered. Only 10 (12.5%) would want government to sell inputs at subsidised rates. Finally, this paper recommends some strategies aim at motivating farmers to accept new agricultural innovations.
Keywords: Government Area; innovations; accepting; Perception; subsidised